Evidence of rare occurrences of the Phoenix effect in the Hawaiian corals Porites compressa and Montipora capitata following mortality induced by a marine heatwave - Jones,Katelyn G.; Barott,Katie L. (PeerJ, 2025)
Coral bleaching is a common stress response to extreme temperatures experienced during marine heatwaves. Bleached corals are left vulnerable without the nutritional support of their algal symbionts, and can often suffer partial or complete mortality. Bleaching-induced mortality is often accompanied by colonization of turf algae over the dead coral skeleton, which can be difficult for corals to regrow over. The Phoenix effect is a phenomenon of rapid recovery of live coral tissue following mortality, which is hypothesized to occur via the regrowth of tissue from deep within the coral skeleton that expands over the top of dead portions. Here, we found that the Hawaiian corals Porites compressa and Montipora capitata can display rapid tissue recovery suggestive of the Phoenix effect. During a marine heatwave that occurred in 2015 in Kāne’ohe Bay, Hawai’i, USA, 237 individuals (including bleached and non-bleached phenotypes) were identified and monitored for mortality and recovery over the next 2–7 years. Nearly 16% of P. compressa individuals and 34% of M. capitata exhibited substantial partial mortality, and approximately half of these affected individuals of each species had bleached during the heatwave. Partial mortality following the 2015 heatwave was followed by turf algae colonization over the exposed skeleton. Of the colonies with substantial mortality, six colonies (10% of affected individuals; five P. compressa and one M. capitata) subsequently recovered to over 90% live coral tissue within 2 years (2017), with an additional three colonies (two P. compressa and one M. capitata) recovering within 4 years of the 2015 marine heatwave (2019). We qualify colonies with rapid tissue recovery as those that meet two criteria: (1) substantial partial mortality (≥40%) in the first 12 months following the initial 2015 marine heatwave, and (2) recovery of any amount of live tissue at anytime before 2022. Interestingly, only colonies that had bleached in 2015 exhibited rapid tissue recovery. A consecutive, yet less severe marine heatwave occurred in 2019, and none of the previously recovered colonies observed experienced significant tissue loss, suggesting these individuals remained resilient amidst a secondary heat stress exposure. This phenomenon is an example of remarkable recovery and resilience that may be informative for further study of mechanisms of coral tissue regeneration in two important reef-building coral species.
Keywords: Coral bleaching; Climate change; Ocean warming; Coral reef; Resilience; Recovery; Kaneohe Bay